2003
DOI: 10.1016/j.hep.2003.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reproductive Factors in Hepatocellular Carcinoma: Impact on Hepatitis B- and C-Related Risk

Abstract: Hepatocellular carcinoma (HCC) is more prevalent in men than in women. Estrogen may play some role in the development of HCC. We conducted a multicenter case-control study to evaluate the effects of reproductive factors on HCC risk, and to assess whether the association between each factor and HCC differs between hepatitis B surface antigen (HBsAg)-positive and -negative women, in which hepatitis C virus (HCV) is the major cause of HCC. The study included 218 women with HCC and 729 control women selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 42 publications
7
74
1
3
Order By: Relevance
“…Lower estrogen activity, either caused by menopause or oophorectomy, is a risk factor for female HCC. 25 We recently showed decreased estrogen receptor-␣ protein in many female HCCs, 26 which could be caused by a mechanism regulated by microRNA-18a. 27 Moreover, Naugler et al demonstrated that estrogens could protect hepatocytes from malignant transformation via down-regulation of interleukin-6 secretion from Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lower estrogen activity, either caused by menopause or oophorectomy, is a risk factor for female HCC. 25 We recently showed decreased estrogen receptor-␣ protein in many female HCCs, 26 which could be caused by a mechanism regulated by microRNA-18a. 27 Moreover, Naugler et al demonstrated that estrogens could protect hepatocytes from malignant transformation via down-regulation of interleukin-6 secretion from Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggests that drinking alcohol and cigarette smoking by women have become more acceptable and increased in Uganda during recent years. Reduced parity is associated with increasing HCC risk among women (Yu et al, 2003). According to the United Nations Population Division data, total fertility rates in Uganda appear to have been stable from 1970 to 1990, with subsequent small annual declines of around 0.5% from 1990 to 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is a known carcinogen for humans, associated with tumors of the breast and endometrium, and possibly the ovary (Yu et al 2003). In addition, there is evidence that increased estrogen exposure can induce a small increased incidence of hepatocellular carcinomas, particularly in young women who are exposed to high-estrogen-containing contraceptive pills (IARC 1999b).…”
Section: Estrogenmentioning
confidence: 99%